Impact of fiber-optic laryngoscopy on the weaning process from mechanical ventilation in high-risk patients for postextubation stridor. Issue 5 (February 2017) - Lemyze, Malcolm; Durville, Emmanuelle; Meddour, Mehdi; Jonard, Marie; Temime, Johanna; Barailler, Stéphanie; Thevenin, Didier; Mallat, Jihad
Abstract : Abstract: The objective of this study was to assess the impact of fiber-optic laryngoscopy (FOL) on the weaning process from mechanical ventilation in critically ill patients with a positive cuff leak test (CLT) as compared with the current recommended strategy based on corticosteroids. In this prospective observational pilot study conducted over a 1-year period in a 15-bed ICU, CLT was systematically performed before extubation in all intubated patients having passed a spontaneous breathing trial (SBT). After the endotracheal tube cuff was deflated, cuff leak volume (CLVol) was assessed during assisted controlled ventilation. When CLT was positive (CLVol < 110 mL), patients either were evaluated using FOL by our half-time FOL-practitioner when present, or received corticosteroids. Among the 233 patients included, 34 (14.6%) had a positive CLT that hampered extubation. Seventeen were treated by corticosteroids and 17 were evaluated by FOL. In the corticosteroids group, the CLVol was still <110 mL at 24 hours in 9 patients (53%). Corticosteroids strategy merely prolonged the total duration of mechanical ventilation (7 [4–11] vs 4 [2–6] days, P = 0.01) by increasing the time between successful SBT and the moment when extubation was effectively achieved (30 [24–60] vs 1.5 [1–2] hours, P < 0.001). This resulted in 2 self-extubations (12%) and 9 FOL-guided extubations (53%) in the corticosteroids group. Massive swelling of the arytenoids was the most common feature shown by FOL. The patients evaluated by FOL who exhibited the thin anterior V-shaped opening of the vocal cords—the V sign—(n = 26, 100%) were immediately extubated without any stridor or respiratory failure afterward. In this pilot study, a FOL-based extubation strategy was feasible and reliable, and significantly reduced the duration of mechanical ventilation in patients with a positive CLT. We describe the "V sign" of FOL that safely allows a successful prompt extubation in patients considered at high risk for postextubation stridor.